Multi-Parametric Study of Convective Heat Transfer in a Magnetized Wavy Cavity Using Hybrid Nanofluids for Thermal Management Applications (European Journal of Pure and Applied Mathematics, 2025)
This study presents a comprehensive numerical investigation of natural convective heat transfer in a wavy-walled enclosure filled with a hybrid nanofluid consisting of copper ( Cu ) and aluminum oxide ( Al2O3 ) nanoparticles dispersed in a water-ethylene glycol (EG) base fluid. Natural convection in such enclosures is widely encountered in electronics cooling, energy devices, and magnetic field-controlled thermal systems, which motivates the present study. A range of water-EG mixture ratios ( 95%−5%, 90%−10%, 80%−20%, 60%−40%, 50%−50%), including the limiting cases of pure water and pure EG, is considered to evaluate the influence of base fluid composition on thermal performance. The aim of this work is to clarify how variations in base fluid ratio,nanoparticle loading, and magnetic field strength affect convective transport. The governing equations are solved numerically using the finite element method to capture coupled buoyancy and magnetohydrodynamic effects. The nanoparticle volume fractions are systematically varied from 0.1% to 0.5% to capture the impact of particle loading, while the Rayleigh number ranges from 103 to 106, and the Hartmann number from 0 to 40 , to assess the effects of buoyancy and magnetic fields. The results show that increasing the Rayleigh number significantly enhances convective heat transfer, while variations in base fluid composition lead to only marginal differences in the average Nusselt number. For example, the average Nusselt number increases by nearly one order of magnitude as Ra rises from 103 to 106, while nanoparticle addition yields up to ∼ 18% enhancement, with copper providing the highest gains. In contrast, increasing Ha from 0 to 40 reduces the heat flux by as much as ∼ 22%. The inclusion of Cu and Al2O3 nanoparticles improves thermal performance, with copper demonstrating a greater enhancement due to its superior thermal conductivity. Furthermore, increasing the Hartmann number suppresses convective currents and reduces the total heat flux, especially near regions of high thermal activity. The wavy geometry intensifies convective mixing and promotes localized heat transfer, with observable peaks in the heat flux distribution aligned with the undulations of the hot wall. These findings highlight the synergistic effects of nanoparticle composition, base fluid selection, magnetic field control, and enclosure geometry on thermal transport, providing valuable insights for designing advanced cooling systems in electronics, energy, and thermalmanagement applications. These insights highlight the relevance of the results for designing advanced cooling systems in electronics, renewable energy devices, and thermal management technologies.
Keywords: Hybrid Nanofluid; Water-Ethylene Glycol Mixture; Wavy Enclosure